Frontline : Preparing Healthcare Systems for Shocks from Disasters to Pandemics - Rentschler, Jun; Klaiber, Christoph; Tariverdi, Mersedeh; Desjonqueres, Chloe; Mercadante, Jared (World Bank, Washington, DC, 2021)
Healthcare systems are at the frontline of delivering critical care during emergencies. Yet, already before the COVID-19 pandemic, many countries were struggling to meet even routine demands for health care. Climate change, disasters, pandemics, and demographic changes will increase pressures on already strained health systems. To strengthen the resilience of health systems to shocks and pressures, this note outlines five principles and priority areas for action. (1) Foundations: Building the capacity of health systems to effectively manage routine demands is a prerequisite for increasing their resilience to shocks. (2) Health care facilities: Facilities must be prepared to meet surge demand during emergencies and protected against shocks, such as earthquakes or floods. (3) Health care systems: Coordinated regional and system-level responses and flexible solutions are key during emergencies. (4) National emergency management: Crisis response by the health sector must be coordinated with emergency management systems, including civil protection and risk financing. (5) Quality infrastructure: Resilient water, electricity, transport, and digital systems are essential for effective health services. The principles presented in this note can help to better prepare health systems to respond to a wide range of shocks, from seasonal demand surges, to pandemics, climate change, and disasters.